T-Cell-Specific Loss of the PI-3-Kinase p110α Catalytic Subunit Results in Enhanced Cytokine Production and Antitumor Response - Aragoneses-Fenoll, Laura; Ojeda, Gloria; Montes-Casado, María; Acosta-Ampudia, Yeny; Dianzani, Umberto; Portolés, Pilar; Rojo, José M. (Frontiers in Immunology, 2018)
Class IA phosphatidylinositol 3-kinase (PI3K) catalytic subunits p110α and p110δ are targets in cancer therapy expressed at high levels in T lymphocytes. The role of p110δ PI3K in normal or pathological immune responses is well established, yet the importance of p110α subunits in T cell-dependent immune responses is not clear. To address this problem, mice with p110α conditionally deleted in CD4+ and CD8+ T lymphocytes (p110α-/-ΔT) were used. p110α-/-ΔT mice show normal development of T cell subsets, but slightly reduced numbers of CD4+ T cells in the spleen. "In vitro", TCR/CD3 plus CD28 activation of naive CD4+ and CD8+p110α-/-ΔT T cells showed enhanced effector function, particularly IFN-γ secretion, T-bet induction, and Akt, Erk, or P38 activation. Tfh derived from p110α-/-ΔT cells also have enhanced responses when compared to normal mice, and IL-2 expanded p110α-/-ΔT CD8+ T cells had enhanced levels of LAMP-1 and Granzyme B. By contrast, the expansion of p110α-/-ΔT iTreg cells was diminished. Also, p110α-/-ΔT mice had enhanced anti-KLH IFN-γ, or IL-4 responses and IgG1 and IgG2b anti-KLH antibodies, using CFA or Alum as adjuvant, respectively. When compared to WT mice, p110α-/-ΔT mice inoculated with B16.F10 melanoma showed delayed tumor progression. The percentage of CD8+ T lymphocytes was higher and the percentage of Treg cells lower in the spleen of tumor-bearing p110α-/-ΔT mice. Also, IFN-γ production in tumor antigen-activated spleen cells was enhanced. Thus, PI3K p110α plays a significant role in antigen activation and differentiation of CD4+ and CD8+ T lymphocytes modulating anti-tumor immunity.